2020
DOI: 10.1093/condor/duaa054
|View full text |Cite
|
Sign up to set email alerts
|

Dunlin subspecies exhibit regional segregation and high site fidelity along the East Asian–Australasian Flyway

Abstract: The degree to which individuals migrate among particular breeding, migration, and wintering sites can have important implications for prioritizing conservation efforts. Four subspecies of Dunlin (Calidris alpina) migrate along the East Asian−Australasian Flyway. Each subspecies has a distinct and well-defined breeding range, but their migration and winter ranges are poorly defined or unknown. We assessed the migratory connectivity of 3 of these subspecies by evaluating a dataset that encompasses 57 yr (1960–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…The authors also found that continued habitat degradation at key sites in the Yellow Sea would likely have a strong negative effect on all 4 Dunlin subspecies, because 21-50% of subspecific migration recoveries were connected to the region. Although these findings are a useful step toward understanding Dunlin migration dynamics on the EAAF, Lagasse ´et al [40] failed to locate any recoveries of the kistchinski subspecies and warned of the likely effects of regionally biased observer effort on regional recovery patterns. The authors were also unable to determine how birds moved between initial capture sites and recovery sites, and consequently, lacked information on the spatial and temporal migration dynamics of the 4 subspecies.…”
Section: Plos Onementioning
confidence: 96%
See 2 more Smart Citations
“…The authors also found that continued habitat degradation at key sites in the Yellow Sea would likely have a strong negative effect on all 4 Dunlin subspecies, because 21-50% of subspecific migration recoveries were connected to the region. Although these findings are a useful step toward understanding Dunlin migration dynamics on the EAAF, Lagasse ´et al [40] failed to locate any recoveries of the kistchinski subspecies and warned of the likely effects of regionally biased observer effort on regional recovery patterns. The authors were also unable to determine how birds moved between initial capture sites and recovery sites, and consequently, lacked information on the spatial and temporal migration dynamics of the 4 subspecies.…”
Section: Plos Onementioning
confidence: 96%
“…By compiling band recoveries, Lagasse ´et al [40] provided the first detailed information on the migration patterns of the 4 Dunlin subspecies that migrate and winter along the EAAF (C. a. actites, arcticola, kistchinski, and sakhalina). In their analysis, the authors found that Dunlin in Japan are predominantly C. a. arcticola, while Dunlin migrating and wintering in other areas of the EAAF may comprise all 4 subspecies.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Study species. The arcticola Dunlin breeds in northern Alaska (and rarely in northwestern Canada) and winters in Asia, along the coasts of China, Japan, Taiwan, North Korea, and South Korea 77,78 . This subspecies is thought to be declining 34,79 , with recent evidence suggesting the loss of non-breeding habitat [39][40][41][42] is causing low annual adult survival 38 .…”
Section: Methodsmentioning
confidence: 99%
“…Migratory connectivity is understood for a growing number of species (Brown et al, 2017; Finch, Butler, Franco, & Cresswell, 2017; Knight et al, 2018, 2021; Lagassé et al, 2020; Trierweiler et al, 2014), which in turn is leading to an increase in empirical evidence of links between connectivity and population dynamics (Hewson, Thorup, Pearce‐Higgins, & Atkinson, 2016; Kramer et al, 2018; Rushing, Ryder, & Marra, 2016). In a study of two migratory songbirds with partially overlapping breeding grounds in North America, breeding populations of both species that overwintered in Central America were stable, whereas populations of one species that overwintered in northern South America, where deforestation was greater, underwent steep declines (Kramer et al, 2018).…”
Section: Introductionmentioning
confidence: 99%